Climatic and environmental risk factors and their role in the prevalence of Fasciola hepatica in water buffalo (Bubalus bubalis) in Mexico - Abel VILLA-MANCERA; Herminio Jiménez-Cortez; Manuel Robles-Robles; Jaime Olivares-Pérez; Agustín Olmedo-Juárez; José Rodríguez-Castillo; Fernando Utrera-Quintana; Alejandro Córdova-Izquierdo; Noemí Pérez-Mendoza (Iraqi Journal of Veterinary Sciences, 2024)
Fasciolosis is a neglected/re-emerging zoonotic disease caused by the trematode Fasciola hepatica that infects both livestock and humans worldwide, causing severe economic losses and public health problems. The study determined the seroprevalence of F. hepatica infection in buffaloes and its associations with age, sex, and climatic/environmental factors (derived from satellite data) to identify potential risk factors from two tropical climate subtypes in two Mexican states. A total of 725 serum samples were analyzed for the presence of anti-F. hepatica immunoglobulin G (IgG) antibodies using an indirect enzyme-linked immunosorbent assay (ELISA), with excretory-secretory (E/S) products as the antigen. The overall prevalence of the parasite in buffaloes between September 2022 and December 2022 was 10.62% (77 out of 725). The highest rate of F. hepatica infection was detected in Veracruz state (9.18%). In addition, the highest prevalence among the climate regions was found in the tropical rainforest (13.62%). In the two states studied, the highest positivity rate for fasciolosis was observed in young animals aged three years and below (21.52%) and in male buffaloes (20.00%). Using multivariate logistic regression analysis, we determined four factors (age, normalized diﬀerence vegetation index, land surface temperature day (LST day), and rainfall) to be significantly associated with an increased risk of parasitic infection. Rainfall was the variable most strongly associated with F. hepatica infection (OR 3.434; 95% CI: 2.181-5.406), followed by LST day (OR 2.832; 95% CI: 1.916-4.186). The results indicate that different factors are significantly associated with the prevalence of liver flukes and highlight the importance of continuous monitoring programs for parasite infections to prevent economic losses in buffalo production.